Molecular and cytological investigations of phosphoglucomutase (PGM1) in the K562 cell line - TOMKINS, J.; FOX, M.; LOVEGROVE, J. U.; PARRINGTON, J.; HOPKINSON, D. A.; WHITEHOUSE, D. B. (Annals of human genetics, 1997)
Phosphoglucomutase 1 (PGM1) deficiency is a stable characteristic of the erythroleukaemic cell line, K562, whereas the activity of the isozymes of the other two PGM loci (PGM2 and PGM3) is slightly elevated. In this study the molecular basis of PGM1 deficiency was investigated by a combined approach utilising protein electrophoresis, immunodetection, cytogenetic techniques, and DNA and RNA analysis. Isoelectric focusing and activity staining confirmed that K562 has no detectable PGM1 activity. Immunoblot analysis of extracts, separated by isoelectric focusing, starch gel and SDS gel electrophoresis, using monospecific anti-PGM1 antibodies showed that K562 contained no detectable immunoreactive material. Karyotype analysis revealed the presence of two intact chromosomes 1 and a derivative chromosome 1, der(1)t(1; 11), each of which carried a copy of the PGM1 gene as demonstrated by fluorescence in situ hybridization using a PGM1 cosmid as probe. Southern blot analysis using a PGM1 cDNA clone as probe suggested that the PGM1 genes had not been subject to any gross structural rearrangements. We were also able to determine that K562 is type PGM1 2+1+ by restriction endonuclease analysis of genomic DNA. Very low levels of PGM1 mRNA which appeared to be full length transcripts were detected in K562 using a reverse transcriptase PCR technique. We conclude that the most likely cause of PGM1 enzyme deficiency in K562 is abnormal regulation of transcription.